The Optimization of Plasma-Activated Water Treatments to Inactivate Salmonella Enteritidis (ATCC 13076) on Shell Eggs - Chia-Min Lin (Foods, 2019)
Egg is a regularly consumed food item. Currently, chlorinated water washing is the most common practice used to disinfect eggs, but this process has a negative environmental impact. A new physical technique, plasma-activated water (PAW), has been demonstrated to possess effective antibacterial activities without long-term chemical residue. In this study, air PAW was used to inactivate Salmonella enterica serovar Enteritidis on shell eggs. Different combinations of activation parameters, including water sources (reverse osmotic (RO) water, tap water), power (40 W, 50 W, 60 W) and activation time (10 min, 20 min, 30 min), were evaluated. The oxidation−reduction potential (ORP) and pH values of each combination were measured, and their antibacterial activity was tested in a bacterial suspension. Higher antibacterial activities, higher ORP values, and lower pH values were obtained with higher power, longer activation time, and lower water hardness. The antibacterial activities of PAW decreased rapidly by increasing the storage time both at room and refrigeration temperatures. Afterwards, RO water was pre-activated for 20 min at 60 W, and then the eggs inoculated with S. enteritidis were placed into PAW for 30 s, 60 s, 90 s, or 120 s with a plasma on-site treatment in the water. More than a 4 log reduction was obtained with 60-s and 120-s treatments. The results showed that the freshness indexes of the eggs treated with PAW were similar to those of the untreated controls and better than those of the eggs treated with commercial processes. In addition, observation under a scanning electron microscope also showed less surface damage of the cuticle on the PAW-treated eggs than on the commercially treated eggs. The results of this study indicate that PAW could be an effective antibacterial agent with less damage to the freshness of shell eggs than commercial methods.